Extrarenal Anaplastic Wilms Tumor: A Case Report With Genomic Analysis and Tumor Models. Issue 4 (4th May 2022) - Willis, Kelsi R.; Sathe, Adwait A.; Xing, Chao; Koduru, Prasad; Artunduaga, Maddy; Butler, Erin B.; Park, Jason Y.; Kurmasheva, Raushan T.; Houghton, Peter J.; Chen, Kenneth S.; Rakheja, Dinesh
Abstract : Primary extrarenal Wilms tumors are rare neoplasms that are presumed to arise from metanephric or mesonephric remnants outside of the kidney. Their pathogenesis is debated but has not been studied, and there are no reports of genomic descriptions of extrarenal Wilms tumors. We describe a diffusely anaplastic extrarenal Wilms tumor that occurred in the lower abdomen and upper pelvis of a 10-year-old boy. In addition to the clinical, histopathologic, and radiologic features, we describe the cytogenetic changes and exomic profile of the tumor. The tumor showed loss of the tumor suppressor AMER1, loss of chromosome regions 1p, 16q, and 22q, gain of chromosome 8, and loss of function TP53 mutation—findings known to occur in renal Wilms tumors. This is the first description of the exomic profile of a primary extrarenal Wilms tumor. Our data indicate that primary extrarenal Wilms tumors may follow the same pathogenetic pathways that are seen in renal Wilms tumors. Finally, we describe the establishment of first ever tumor models (primary cell line and patient-derived xenograft) from an extrarenal Wilms tumor.